Proses Produksi Program Podcast Berbasis Audio-Visual sebagai Media Penyebaran Informasi Proses Kreatif Musisi Pop Bali - Irene Nyoman Esterina Pregie Angga Dewi; Ricky Irawan; I Komang Darmayuda; Wahyu Sri Wiyati (Journal of Music Science, Technology, and Industry, 2022)
Purpose: This research is to understand the production process of audio-visual-based podcast programs as a media for disseminating information on the creative process of Balinese pop musicians. Research Methods: In this internship program for the MBKM (Merdeka Belajar Kampus Merdeka) program, the authors and partner i.g. Bali TV want to produce a podcast program with the aim of preserving Balinese Pop Music culture which is currently experiencing global challenges in the context of the industrial revolution 4.0. Results and Discussion: The presence of podcasts is a form of development from conventional radio media which previously would have been one of the most popular media. Currently, podcasts are in great demand because podcasts have various advantages compared to radio, namely podcasts are on demand (the control of the podcast is on its listener). The convenience and advantages offered by podcasts provide a new platform for the dissemination of information widely. Implication: Music programs that exist today are considered only able to fulfill the purpose of being an entertainment and promotion. For this reason, a podcast program that presents speakers who are engaged in their fields and also provides information about the creative process of Bali Pop musicians is considered to be a form of preserving Bali Pop Music from now onwards.